Short-term Heat Application Reduces Itch Intensity in Atopic Dermatitis: Insights from Mechanical Induction and Real-life Episodes - Joachim W. Fluhr; Leonie Herzog; Razvigor Darlenski; Tim Mentel; Torsten Zuberbier (Medical Journals Sweden, 2024)
Heat application is known to activate transient receptor potential (TRP) channels, which play a crucial role in sensory perception, including itch. In this study, the effect of a 5-s, 49°C heat application on itch intensity in atopic dermatitis (AD) patients was evaluated. The study comprised 2 parts: a controlled trial investigating the impact of brief heat treatment on mechanically induced itch, and a real-life study of AD patients experiencing itch attacks. A significant and immediate reduction in itch sensations following heat application was shown, with effects enduring over time. This response, however, showed notable individual variability, underscoring the potential of personalized approaches in AD treatment. Repeated applications of heat showed no habituation effect, suggesting its viability as a non-pharmacological, patient-tailored option for managing itch in AD. Further research in larger cohorts is warranted to refine treatment protocols and deepen understanding of the mechanisms involved.